Evaluation of tarsal injuries in C57BL/6J male mice - Kick, Brenda L.; Anderson, Laura; Doty, Rosalinda; Wooley, Christine; Dyer, Meaghan; Green, Torrian; Knickerbocker, Veronica; Brown, Zoe; Loeber, Samantha; Wotton, Janine; Lyons, Bonnie; Waterman, Linda; et al. (PloS one, 2023)
Tarsal joint abnormalities have been observed in aged male mice on a C57BL background. This joint disease consists of calcaneal displacement, inflammation, and proliferation of cartilage and connective tissue, that can progress to ankylosis of the joint. While tarsal pathology has been described previously in C57BL/6N substrains, as well as in STR/ort and B10.BR strain, no current literature describes this disease occurring in C57BL/6J mice. More importantly the behavioral features that may result from such a change to the joint have yet to be evaluated. This condition was observed in older male mice of the C57BL/6J lineage, around the age of 20 weeks or older, at a frequency of 1% of the population. To assess potential phenotypic sequela, this study sought to evaluate body weight, frailty assessment, home cage wheel running, dynamic weight bearing, and mechanical allodynia with and without the presence of pain relief with morphine. Overall mice with tarsal injuries had significantly higher frailty scores (p< 0.05) and weighed less (p<0.01) compared to unaffected mice. Affected mice had greater overall touch sensitivity (p<0.05) and they placed more weight on their forelimbs (p<0.01) compared to their hind limbs. Lastly, when housed with a running wheel, affected mice ran for a shorter length of time (p<0.01) but tended to run a greater distance within the time they did run (p<0.01) compared to unaffected mice. When tested just after being given morphine, the affected mice performed more similarly to unaffected mice, suggesting there is a pain sensation to this disease process. This highlights the importance of further characterizing inbred mouse mutations, as they may impact research programs or specific study goals.